Epidemiological investigation of an outbreak of hepatitis A in rural China. (April 2015) - Yu, Ping; Huang, Lihong; Li, Hui; Liu, Mingbin; Zong, Jun; Li, Chao; Chen, Feng
Highlights: An outbreak of hepatitis A in rural China was investigated. The epidemic curve and transmission chain suggested a person-to-person transmission pattern. The case–control study showed that close contact with infectious cases was a risk factor, and hand-washing was a protective factor. No evidence could be found of a common water or food item as the source of this hepatitis A outbreak. Summary: Objectives: This investigation was a response to an outbreak of hepatitis A in rural China in 2013. The objectives were to identify the pattern of transmission and the risk factors. Methods: A probable case was defined as an individual in/nearby the village of the outbreak with jaundice and/or an elevation of serum alanine aminotransferase (at or above 80 IU/l) plus at least three of the following symptoms: fever (axillary temperature ≥37 °C), headache, nausea, vomiting, anorexia, or abdominal pain in the upper right quadrant, during the outbreak period (from June 1 to August 11, 2013). Using a case–control study design, we compared exposures to suspected food items, water, and close contact with a patient or case with asymptomatic infection between 22 cases and 32 controls. Results: We identified 22 cases, including 15 symptomatic cases and seven with asymptomatic infections. All cases were aged <15 years. Household clustering was apparent (Chi-square = 4.69, p < 0.05). Contact with symptomatic cases or cases with an asymptomatic infection was a major risk factor (59.09% in cases and 25.00% in the controls: odds ratio (OR) 4.33, 95% confidence interval (CI) 1.17–16.68). A good hand-washing habit (at least once per day) was found in 45.45% of cases vs. 78.13% of controls (OR 0.23, 95% CI 0.06–0.88). The dose–response analysis showed that the daily frequency of hand-washing was inversely associated with infection (trend Chi-square = 5.35, p = 0.021). Person-to-person transmission was deduced from the epidemic curves and the transmission chain of symptomatic cases. Conclusion: The pattern of transmission in this outbreak was person-to-person, and the transmission route was indicated to be fecal–oral. In addition to close contact, insufficient hand-washing was a risk factor. Strengthening the management of the rural environmental sanitation services and enhancing awareness in the household are key to preventing outbreaks of hepatitis A in the future.